IMPROVING STUDENTS’ READING COMPREHENSION ON NARRATIVE TEXT BY USING STORY MAPPING TECHNIQUE - Weli Bernado Tamsil; Sofian Sofian; Eusabinus Bunau (Universitas Tanjungpura, 2020)
AbstractThis research was conducted in order to improve students’ reading comprehension in narrative text using Story Mapping Technique to the eleventh-grade students. The form of this research is classroom action research. The subjects were 28 students of grade XI IIS 2 students of SMA Taman Mulia Kubu Raya in Academic Year 2019/2020. The data were collected using tests, observation checklists, and field notes. From the observation checklist and field notes, it was found that all of the students participated to the activity and did their task well. Teaching reading comprehension on narrative text by using story map technique positively helps the students organize their ideas into a map which help them to integrate the concepts and idea from the story. The students gave positive response to the explanation of narrative text and could use the story mapping technique properly and the students’ mean score improved from 64.29 in cycle one (36% students passed the minimum score) to 76.08 in cycle two (72% students passed the minimum score). In conclusion, it can be inferred that story mapping technique improved students’ reading comprehension skill in narrative text. Keywords: Narrative text, Reading, Story Mapping Technique.